Comparison of the Components of Perservance Literature in two Important Poets of Ghaznavi era: Sanayi and Masoud Sa’d Salman - Naimi, Elham (2020)
Throughout the history of Persian literature, there have been poets who have fueled the Persian literary treasures with their capable pen. In that sense, this article specifically examines and compares the poems of the sustainability of the two innovative and owners of style in Qaznavid era. On the one hand, Sanayi established a kind of social and critical poetry. Gnostic and Qalandar poetry with its lyrics and He freshened the religious doctrine with his Masnavis and expressed religious issues in the form of stories. On the other hand, the issues of sustainability literature are clearly evident in all of its poetic forms. Topics such as the fight against oppression and poverty, the invitation to lasting peace and the promotion of religious ethics. Masood Sa’d is one of the elite innovators of the Ghaznavi era, and his Habsiyeh (imprisonment), Shahrashoub, and his enchants show the genius of his poetry. His utilization of the components of sustainability is very significant especially in his imprisonment, and in other types of poetry, he has less. The present study tried to investigate these components regarding the limitations of article structure from a comprehensive perspective after careful study of the works of these two poets and acheiving the outstanding examples of sustainability literature.